Manikin test for flame engulfment evaluation of protective clothing: Historical review and development of a new ISO standard - Camenzind, M. A.; Dale, D. J.; Rossi, R. M. (Fire and materials, 2007)
The overall performance of a firefighter turnout suit can only be evaluated using both bench‐scale tests and an assessment based on an instrumented manikin under defined, close to real‐life conditions in a laboratory. Using manikins in rating protective clothing has already a long history which will be reflected in this paper. Efforts all over the world to reproduce a flame engulfment situation in a laboratory are currently being combined in a new draft international standard (ISO/DIS 13506.3). A round robin test showed an acceptable reproducibility for this method based on a manikin test and a gas burner system. An overview of existing measurement systems and the results of this round robin are discussed and possible improvements for the standard flame engulfment test method are proposed. Copyright © 2006 John Wiley & Sons, Ltd.